New Tech, Old Fuel. - Michael Dumiak
Upon extraction, the oil shale found is Estonia can be pulverized and burned like coal to drive electric generators. However, burned shale produces millions of metric tons of ash as well as airborne particles laced with heavy metals. The state-owned Eesti Energia in Tallinn has developed a means to address this environmental problem. The Eesti plant has installed the first of what will be 16 new circulating fluidized bed boilers, which drastically reduce emissions from burning oil shale. Eesti plans to implement a new disposal technology that will address its problem with the ash pool
Keywords: Eesti Energia; Estonia; Foster Wheeler; Airborne particles; Ash; Climate change; Disposal technology; Fire rock; Independent energy source; Oil shale technology